2007
DOI: 10.1111/j.1600-0560.2006.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of class II β‐tubulin in non‐melanoma cutaneous tumors

Abstract: Class II tubulin expression is closely related to squamous or follicular differentiation and may be helpful in distinguishing most SCCs from KAs and BCC from TE. However, it does not reliably distinguish well-differentiated, crateriform SCC from KA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Tubulin is known to form microtubules and the centrosome and is an important protein in the differentiation of cells including keratinocytes (34). Both α and β-tubulin decreased in alopecic mice ( Table I), suggesting that cell proliferation of keratinocyte was decreased in alopecic mice.…”
Section: Discussionmentioning
confidence: 97%
“…Tubulin is known to form microtubules and the centrosome and is an important protein in the differentiation of cells including keratinocytes (34). Both α and β-tubulin decreased in alopecic mice ( Table I), suggesting that cell proliferation of keratinocyte was decreased in alopecic mice.…”
Section: Discussionmentioning
confidence: 97%
“…However, ß II expression is not directly associated with neuroendocrine differentiation in the cutaneous tumors, because ß II is expressed in the keratinocytes of the granular layer, hair cortical and cuticular cells, inner root sheath and companion layer of the outer root sheath in the normal skin and up-regulated during squamous differentiation of keratinocytes (20). Roh et al also reported that ß II expression was increased in the areas of squamous or follicular differentiation in the cutaneous tumors (19). Thus, ß II expression in BCCs is likely not the predominant phenotype related to the neuroendocrine differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…It is widely distributed in the developing neuronal axons and dendrites as well as neuroepithelial tumors and represents a marker for progenitor and neuronal stem cells (18). Roh et al reported that ß II was focally expressed in approximately half of BCCs (32/57 cases) (19). However, ß II expression is not directly associated with neuroendocrine differentiation in the cutaneous tumors, because ß II is expressed in the keratinocytes of the granular layer, hair cortical and cuticular cells, inner root sheath and companion layer of the outer root sheath in the normal skin and up-regulated during squamous differentiation of keratinocytes (20).…”
Section: Discussionmentioning
confidence: 99%
“…Isotype expression differs amongst cancers. βIII has been detected as a potential marker in squamous, ovarian, and neuroendocrine cancer [20][21][22], while βII-tubulin has been proven to be useful in differentiating skin tumors and predicting the response to treatment in prostate cancer [23,24]. For colorectal cancer, tubulin expression has been correlated with disease stage [25,26], while analysis of colorectal cancer cell lines has revealed the predominant expression of βI, Fig.…”
Section: Discussionmentioning
confidence: 99%